Legal Review of the Validity of Electronic Deeds in International Business Transactions: An Indonesian Notary's Perspective - Mega Wulandari (Publikasi Indonesia, 2025)
The development of digital technology has encouraged the use of Actelectronic in international business transactions. However, the validity of electronic activities is still a legal issue, especially in Indonesia, where regulations are not fully in line with international standards such as the UNCITRAL Model Law on Electronic Commerce. This study aims to analyze the validity of electronic deeds in international business transactions through the perspective of Indonesian notaries to identify existing challenges, as well as provide recommendations for regulatory harmonization. This research uses a normative juridical method with a legal and regulatory approach, a study of legal doctrine, and an analysis of international standards related to electronic transactions. Primary data were obtained from regulatory studies such as the ITE Law and the Notary Position Law, while the data secondary comes from international standards such as UNCITRAL Model Law and eIDAS. The results of the study show that although electronic deeds are recognized by the ITE Law as a valid legal evidence tool, their application in cross-border transactions is constrained by inconformities with the Notary Position Law, which still requires physical presence and manual signatures. In addition, the lack of integration with international standards and inadequate cybersecurity infrastructure are also major obstacles. The discussion highlighted the importance of harmonization of national regulations with international standards.